Phosphorous dendrimer bound polyethyleneimine as solid sorbents for post-combustion CO2 capture - Thompson, Samuel J.; Soukri, Mustapha; Lail, Marty (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Covalently tethered amines afford a robust, water-stable CO2 sorbent.•Sorbent capacities for CO2 as high as 13.6 wt% under simulated flue gas conditions.•No degradation observed over 350 cycles or 700 contiguous running hours. High capacity solid amine sorbents for CO2 adsorption were prepared via a cross-linking reaction between polyaldehyde phosphorous dendrimers and polyethyleneimines (PEIs). The best performing sorbent achieves an average CO2 capacity of 13.1 wt% through 350 cycles of adsorption/desorption over 700 contiguous hours from simulated flue gas conditions (CO2, O2, H2O, and N2). The adsorption operates with relatively high capacities and rapid kinetics between 25 and 85 °C, reaching 90% capacity within the first 10 min of exposure at 65 °C. The capture of CO2 in the presence of common acid gas contaminants (SO2, NO, and NO2) and from sour gas (10,000 ppm H2S) was also demonstrated. The heat of adsorption and other physical properties (e.g. surface area, pore volume, and SEM) were measured and disclosed.